Comparative Evaluation of the WHO Labour Care Guide and Modified Partograph in Cesarean Section Frequency, Delivery Outcomes, and Maternal Stress in Tertiary Care Hospitals in Hyderabad - Shua Bano; Fahmida Parveen; Pulwisha Mustafa; Amna Aslam; Afshan Sultan Zia; . Paras (Pakistan Journal of Health Sciences, 2026)
The global rise in cesarean section (CS) rates has raised concerns due to associated maternal and neonatal risks, increased healthcare costs, and psychological stress. To address this issue, the World Health Organization introduced the Labour Care Guide (LCG) as an updated, evidence-based tool for monitoring labour and improving childbirth outcomes. Objectives: To compare the frequency of cesarean sections among women managed using the WHO Labour Care Guide (LCG) and those managed with the Modified Partograph in tertiary care hospitals of Hyderabad, Sindh. Methods: A comparative cross-sectional study was conducted at Liaquat University Hospital and Khidmat-e-Khalq Foundation Hospital over four months. A total of 430 pregnant women were enrolled, with 215 participants in each group. Maternal stress levels were assessed using the Perceived Stress Scale (PSS). Data were analyzed using SPSS version 26.0, and the Chi-square test was applied to compare categorical variables. Results: Women managed with the LCG had a significantly lower CS rate compared with those monitored using the Modified Partograph (40 vs. 65; p=0.02). The LCG group also demonstrated improved neonatal outcomes, including higher birth weights and better Apgar scores. Additionally, maternal stress levels were significantly lower and satisfaction with care was higher among women in the LCG group (p